Cladistic assessment of subtribal affinities within the tribe Moriomorphini with description of Rossjoycea glacialis, gen. n. and sp. n. from the South Island, and revision of Meonochilus Liebherr and Marris from the North Island, New Zealand (Coleoptera, Carabidae) - James Liebherr (ZooKeys, 2011)
Phylogenetic relationships within the tribe Moriomorphini Sloane, 1890 are analyzed cladistically based on 75 morphological characters and 21 ingroup terminal taxa rooted at a Trechus obtusus Erichson outgroup. Based on the resultant cladistic relationships, two subtribes–Moriomorphina and Amblytelina Blackburn, 1892–are recognized, with the following new synonymies proposed: Meonides Sloane, 1898 = Amblytelina (NEW SYNONYMY); Tropopterides Sloane, 1898 = Amblytelina (NEW SYNONYMY); Mecyclothoracitae Jeannel, 1940 = Amblytelina (NEW SYNONYMY). Monophyly of Moriomorphina is based on presence of elongate, parallel-sided and glabrous to nearly glabrous male parameres, whereas Amblytelina are defined most broadly by possession of conchoid parameres with narrowed, setose apices, subtending a clade defined by a more derived parameral configuration whereby elongate styloid parameres terminate in a whip-like apical extension. Representatives of all New Zealand moriomorphine genera are included in the analysis, with cladistic results necessitating description of Rossjoycea glacialis, gen. n. and sp. n., known from a single locality near the Franz Josef Glacier, Westland, South Island, New Zealand. Monophyly of Meonochilus Liebherr and Marris, 2009 is demonstrated, and its six species are taxonomically revised: M. amplipennis (Broun), M. eplicatus (Broun), M. placens (Broun), M. bellorum, sp. n., M. rectus, sp. n., and M. spiculatus, sp. n. Geographic restriction of Meonochilus to the North Island of New Zealand, coupled with its sister-group status to an Australian-based Amblytelus Erichson-Mecyclothorax Sharp clade reinforce the interpretation that Meonochilus was isolated in New Zealand by vicariance along the Norfolk Ridge, subsequent to New Zealand’s initial Cretaceous isolation from Tasmania and southeastern Australia via opening of the Tasman Sea.